Peningkatan Kompetensi Sumber Daya Manusia di Era Digital pada Pegawai Lembaga Pendidikan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Sari, Ratna; Sugiarti, Endang; Prasetiyani, Desi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid development of digital technology demands that educational institutions continuously enhance the competencies of their human resources to stay relevant and effective. This Community Service Program (PKM) aimed to improve the digital competencies of staff at the Tajaul Karomah Education Institute in Situ Gadung Village, Tangerang Regency. The main objective was to equip teachers, administrative staff, and students with the necessary knowledge and skills to adapt to and utilize digital tools effectively in their educational and administrative activities. The PKM was conducted on May 3–4, 2025, at the Tajaul Karomah School by a team of 15 lecturers from Universitas Pamulang. The activity involved 45 participants, including teachers, administrative staff, and students. The implementation consisted of three stages, preparation, execution, and reporting. During the execution stage, the PKM team used a combination of lectures, hands-on practice, discussions, and Q&A sessions to deliver the training. As a result, participants showed a marked increase in understanding and ability to operate various digital tools and platforms relevant to their roles. Feedback indicated high satisfaction and a strong desire for continued training in digital literacy. This PKM has contributed significantly to enhancing the digital competency and readiness of educational human resources in the region.